In situ study on interactions between hydroxyl groups in kaolinite and re-adsorption water. Issue 29 (30th April 2020) - Han, Yanna; Yan, Zhuangzhuang; Jin, Lijun; Liao, Junjie; Feng, Guorui
Abstract : Because two layers slipped away from each other, inner-surface O–H was transformed into outer O–H during heating from 100–300 °C. Re-adsorption water could be thoroughly removed at 650 °C. Abstract : The interactions between O–H groups in kaolinite and re-adsorption water is an important aspect that should be considered in the hydraulic fracturing method for the production of shale gas, because the external water adsorbed by kaolinite in shale would significantly affect the desorption of methane. In this study, the interactions were investigated via changing the amount of O–H groups and re-adsorption water in kaolinite by heating treatment and water re-adsorption. To overcome the overlap of IR vibration bands of the O–H functional groups in H2 O and those in parent kaolinite, kaolinite samples with D2 O re-adsorption were prepared by drying the H2 O from raw kaolinite and soaking the dried kaolinite in D2 O. The interactions between O–H groups in kaolinite and D2 O molecules were investigated by in situ DRIFT and TG-MS. The results demonstrated that the vibration at 3670 ± 4 cm −1 in the DRIFT spectra could be due to the outer O–H groups of the octahedral sheet on the upper surface of the kaolinite microcrystal structure, rather than a type of inner-surface O–H group. All types of O–H groups, including the inner O–H groups in kaolinite, could be transformed into O–D groups after D2 O re-adsorption at room temperature. The inner-surface O–H groups in kaolinite are the most preferred sites for D2 O re-adsorption; thus, they would be the key factor for studying the effect of re-adsorption water on methane desorption. When the temperature increased from 100 °C to 300 °C, two layers of kaolinite slipped away from each other, resulting in the transformation of inner-surface O–H groups into outer O–H groups. Thus, the temperature range of 100 to 300 °C was suggested for the heat treatment of kaolinite to decrease the content of inner-surface O–H groups; thereby, the amount of re-adsorption water was reduced. However, to thoroughly remove the re-adsorption water, a temperature higher than 650 °C should be used.